Practices Promoting Social Interaction and Dialogue in the Context of Organizational Change - Kedonperä, Saara (My University, 2019)
Aim: The purpose of this study is to examine how to facilitate social interaction and dialogue in the context of organizational change. Attention has been paid to human involvement and the role of social interaction and dialogue in bringing about organizational change. The study aims to advance the understanding of the underexplored topic. Framework: The research topic is studied through the strategy-as-practice (SAP) and organizational change literature. SAP provides lenses to study the actual doing in an organization. Especially, the concept of practices is utilized to examine everyday activities that facilitate social interaction and dialogue during the change. Organizational change is examined through the lenses of social constructionism. Organizational change is seen as a social process as being constituted through everyday interactions and discourses among actors. Methodology: The area of research is complex and relatively less known, which is why a case study strategy is utilized. A single-case design is used because a specific organization operating in the Hospital, Rehabilitation and Care Services division in Helsinki is studied. The empirical material is collected through 15 semi-structured interviews and discourse analysis is used as a means to analyze social action and discourses among employees. Findings: The findings suggest that in order to bring about change, social interaction and dialogue can be facilitated with a range of practices. A total of 15 practices were found. The practices are grouped into five categories according to the nature of practices: discursive activities, operating principles, episodic practices, social norms, and material and spatial aspects.
Keywords: strategy-as-practice; practice; organizational change; social constructionism; fi=Johtaminen ja organisaatiot|en=Management and Organization|; fi=Master’s Programme in Strategic Business Development|